A new bare-soil index for rapid mapping developing areas using LANDSAT 8 data - S. Li; X. Chen (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2014)
One of the most basic classification tasks is to distinguish bare-soil areas from urban region. Bare-soil plays an important role in the ecosystem. It could be the reason of dust storms and the indicator of urban expansion. It is also important to monitor the bare-soil areas, but there was no good idea to automatically extraction bare-soil areas using existing method. In this work, a new bareness index (BI) has been developed and applied to map developing region in Pearl River Delta using Landsat OLI/TIRS data in 2013. The BI based on the logical combination of the Tasseled Cap transformation (TCB) and Normalized Difference Bareness Index (NDBaI). Results show that the BI not only has a good effect on the enhancement of bare soil information, but also on the inhibition of the background information, and improve the accuracy of detection. The results of this study could be of scientific and practical merits in regional remote sensing monitoring and improve the accuracy of land use classification.